ficwriter17
ficwriter17
19-10-2019
Mathematics
contestada
If f(x) = 2x + 9, then f(-1) = _____.
Respuesta :
max3496
max3496
19-10-2019
F(-1)= 7
It’s equal 7 because
You substitute (-1) for (x)
Now the work is f(-1)= 2(-1) + 9
2*-1 is -2 then you add -2 with 9 and you get 7 Which is your answer
Hope I helped
Answer Link
joeyvbeast
joeyvbeast
09-07-2021
Answer: 7
Step-by-step explanation:
f(x)= 2x + 9
f(x) = 2 x -1 + 9
2 x -1= -2
-2 + 9 = 7
Answer Link
VER TODAS LAS RESPUESTAS ( 88+ )
Otras preguntas
Which of the following metal atoms would have the highest conductivity? A.the atom with the smallest radius and the fewest valence electrons B.the atom with the
How many ounces are equivalent to 25 pounds?
Is jimmy carter underrated
What are the steps for the scientific method?
onur come on :D modlar pislikler nefret ediyorum :D
what systems contain the heart
One of the first things Vladimir I did after he became the ruler of Kiev was to
Which is the central meridian of uae and it passes through which state
Write the expression in simplest form. Assume that all variables are positive.
What does 5/6 equal as a decimal?
ACCESS MORE